Research protocol for a digital intervention to reduce stigma among males with a personal experience of suicide in the Australian farming community - Alison J. Kennedy; Vincent Lawrence Versace; Susan A. Brumby (BMC, 2016)
Abstract Background Australian farming communities have up to twice the suicide rate of the general population. Men, particularly, demonstrate debilitating self- and perceived-stigma associated with an experience of suicide. The Ripple Effect is aimed to reduce suicide stigma within the social, cultural, geographical and psychological contexts in which it occurs. Methods A mixed-method design with multi-level evaluation will be effected following the development and delivery of a personalised website experience (combining shared stories, education, personal goal setting and links to resources) to farming men, aged 30-64 years, with an experience of suicide. Pre- and post-surveys will be used to assess changes in self- and perceived-stigma and suicide literacy. Online feedback from participants and semi-structured interviews during follow-up will be thematically analysed. Discussion This project will provide information about increasingly accessible, innovative approaches to reducing the debilitating health and wellbeing effects of suicide stigma on a population of Australia's farmers. Trial registration This research protocol was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) (ACTRN: ACTRN12616000289415 ) on 7th March, 2016.